Preoperative Radiotherapy and Wide Resection for Soft Tissue Sarcomas: Achieving a Low Rate of Major Wound Complications with the Use of Flaps. Results of a Single Surgical Team - Chan, Lester Wai Mon; Imanishi, Jungo; Grinsell, Damien Glen; Choong, Peter (Frontiers in Surgery, 2018)
Background: Surgery in combination with radiotherapy (RT) has become the standard of care for most soft tissue sarcomas. The choice between pre and post-operative RT is controversial. Pre-operative RT is associated with a 32-35% rate of major wound complications (MWC) and 16-25% rate of re-operation. The role of vascularized soft tissue “flaps” in reducing complications is unclear. We report the outcomes of patients treated with pre-operative RT, resection and flap reconstruction. Patients and Methods: 122 treatment episodes involving 117 patients were retrospectively reviewed. All patients were treated with 50.4Gy of external beam radiation. Surgery was performed at 4-8 weeks after completion of RT by the same combination of orthopaedic oncology and plastic reconstructive surgeon. Defects were reconstructed with 64 free and 59 pedicled/local flaps. Results: 30(25%) patients experienced a MWC and 17(14%) required further surgery. 20% of complications were exclusively related to the donor site. There was complete or partial loss of three flaps. There was no difference in the rate of major wound complication or re-operation for complications with respect to age, sex, tumour site, previous unplanned excision, tumour grade, depth and type of flap. Tumour size ≥8cm was associated with a higher rate of re-operation (11/44 vs 6/78; P=0.008) but the rate of MWC was not significant (16/44 vs 14/78; P=0.066). Conclusions: The use of soft tissue flaps is associated with a low rate of MWC and re-operation. Our results suggest that a high rate of flap usage may be required to observe a reduction in complication rates.